2019
DOI: 10.1021/acs.iecr.9b00354
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microchannel Synthesis Strategy for Continuous Fabrication of Nanosized γ-CuI and Their Photocatalytic Performance

Abstract: A novel microchannel synthesis route for continuous synthesis of nanosized copper iodide (γ-CuI) using hydrated hydrazine as reducing agent was proposed. We continuously produced γ-CuI spherical nanoparticles in 99% yield and grain size of ca. 44−100 nm. Furthermore, the utilization of hydrated hydrazine was essential in precluding powder plugging the microchannel by self-generated N 2 . The microreaction process conditions, such as residence time, pH value, temperature, and reactant concentration, had great i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…18 As a photocatalyst, CuI has received much attention in recent years for degrading organic pollutants in water. 19,20 CuI is combined with photocatalysts such as BiOBr, 21 g-C 3 N 4 22 and FePO 4 23 to form heterojunctions, which exhibit remarkably improved photocatalytic activity for degrading organic pollutants in water. The CuI/BiOI shows enhanced photocatalytic activity, 24,25 and the CuI/g-C 3 N 4 exhibits efficient photocatalytic hydrogen evolution.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 As a photocatalyst, CuI has received much attention in recent years for degrading organic pollutants in water. 19,20 CuI is combined with photocatalysts such as BiOBr, 21 g-C 3 N 4 22 and FePO 4 23 to form heterojunctions, which exhibit remarkably improved photocatalytic activity for degrading organic pollutants in water. The CuI/BiOI shows enhanced photocatalytic activity, 24,25 and the CuI/g-C 3 N 4 exhibits efficient photocatalytic hydrogen evolution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, researchers prepared many ZnO-based photocatalysts by ion doping, metal deposition and heterostructure construction, such as Cr-doped ZnO, Cu-doped ZnO, Ag/ZnO, Pt/ZnO, MoS 2 /ZnO, Bi 2 O 3 /ZnO and ZnO/Ti 3 C 2 . As a photocatalyst, CuI has received much attention in recent years for degrading organic pollutants in water. , CuI is combined with photocatalysts such as BiOBr, g-C 3 N 4 and FePO 4 to form heterojunctions, which exhibit remarkably improved photocatalytic activity for degrading organic pollutants in water. The CuI/BiOI shows enhanced photocatalytic activity, , and the CuI/g-C 3 N 4 exhibits efficient photocatalytic hydrogen evolution .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microfluidic technology has attracted increasing attention across various fields due to its precise control and high operational efficiency. Enhanced mass transfer within the microchannel enables the continuous execution of certain synthetic processes, thus ameliorating the productivity of products traditionally inefficient in complex batch operations. Segmented flow, one of the most studied flow patterns in microfluidics, features a vortex in each segment, facilitating robust internal recirculation and superior mass and heat transfer. Owing to this attribute, segmented flow has been utilized not only in chemical reactions but also in extraction and crystallization procedures. In our previous study, we effectively regulated the length of the gas–liquid segment in a 1.59 mm perfluoroalkoxy (PFA) tube without varying the fluid flow rates . We further demonstrated that mass transfer at the segment interface is significantly enhanced relative to that at the bubble surface, and the rate of mass transfer can be modulated by altering the segment length, a topic to be elaborated upon in our upcoming publication.…”
Section: Introductionmentioning
confidence: 99%